Star-crossed Clusters: Asteroseismic Ages for Individual Stars Are in Tension with the Ages of Their Host Clusters - Jamie Tayar; Meridith Joyce (The Astrophysical Journal Letters)
A meta-analysis of seismic ages determined for individual stars in the well-studied open and globular clusters NGC 6819, NGC 6791, M67, M4, M19, M80, and M9 reveals both high variance across measurements and a possible discrepancy with independent, isochrone-based age determinations for the clusters in which these stars reside. The scatter among asteroseismic ages for individual stars in any one of these clusters far surpasses both the absolute age uncertainty computed for reference cluster M92 (5.4%) and the model-to-model systematic uncertainties in isochrones (roughly 10%). This suggests that either binary processes are significantly altering the masses of stars in these clusters, or some additional corrections, perhaps as a function of mass, metallicity, or surface gravity, are required to bring the asteroseismic age scale into concordance with ages inferred from isochrone or similar model fitting.